Bioavailability of Plant-Derived Antioxidants - Ehab A. Abourashed (MDPI AG, 2013)
Natural products with antioxidant properties have been extensively utilized in the pharmaceutical and food industry and have also been very popular as health-promoting herbal products. This review provides a summary of the literature published around the first decade of the 21st century regarding the oral bioavailability of carotenoids, polyphenols and sulfur compounds as the three major classes of plant-derived antioxidants. The reviewed original research includes more than 40 compounds belonging to the above mentioned classes of natural antioxidants. In addition, related reviews published during the same period have been cited. A brief introduction to general bioavailability-related definitions, procedures and considerations is also included.